Process of Distribution and Conditions for the Opening of Stationary Cinemas in the Cities of the Tobolsk Province at the Beginning of the 20th Century - E. A. Yunina (Научный диалог)
On the basis of archival materials introduced into scientific circulation, analysis of regional periodicals, reference books, normative acts and published data, the history of the emergence and spread of stationary cinematic theaters in the Tobolsk province is traced. The administrative and institutional aspect of their opening is considered. Particular attention is paid to preparatory work, technical and construction rules and conditions for the official acceptance of buildings, fire safety measures of pre-revolutionary cinematographs, toponymy and their localization in the socio-cultural space of cities. The article provides information on the social and professional affiliation of the owners of the electric theaters. It is concluded that the positive dynamics of the founding of cinematographs in the studied region, characterized by speed and continuity, refers to the period 1909—1916. The organization of a network of cinemas in the provincial cities of the West Siberian part of Russia was associated with the work of provincial institutions, municipal authorities, and police officers. The functioning of these public institutions was systematically monitored by the officials of these departments, who were guided by the technical normative legal acts adopted in the empire that regulate the conditions for keeping cinemas. The development of cinematography was an important indicator of the innovative trends taking place in the leisure segment of the everyday life of citizens.